PENGARUH TRANSPARANSI DAN AKUNTABILITAS TERHADAP PENGELOLAAN KEUANGAN DESA DENGAN SIFAT AMANAH SEBAGAI VARIABEL MODERASI - Rama Linda Septian; Andi Wawo; Raodahtul Jannah (Universitas Islam Negeri Alauddin Makassar, 2021)
This study aims to determine the effect of transparency and accountability on village financial management with the nature of trust as a moderating variable (study in the village of Pallangga sub-district, Gowa district). This research is a quantitative research with associative research approach. The population in this study is a village in the sub-district of Pallangga, Gowa district. The sampling technique in this study was purposive sampling, while the sample in this study was village officials in the Pallangga district, Gowa district. The method of data collection is using a questionnaire that is distributed directly. The data used in this study is primary data collected through a questionnaire survey. The results of this study indicate that transparency and accountability have a significant positive effect on village financial management. Meanwhile, the nature of trust cannot moderate the effect of transparency and accountability on village financial management.